Cardiovascular effects of intracerebroventricular bicuculline in rats with absence seizures - (:unkn) unknown (ELSEVIER SCIENCE BV, 1999)
Gamma-aminobutyric acid (GABA) plays an important role in both central cardiovascular homeostasis and pathogenesis of epileptic seizures. Previous studies have indicated a critical role of the amygdala in the spread of seizures from brainstem to forebrain and in the regulation of autonomic responses such as blood pressure and heart rate. The purpose of the present study was to examine blood pressure and heart rate effects of bicuculline, a GABA(A) antagonist, and the effect of lesions of the central or the basolateral nuclei of the amygdala on bicuculline-induced cardiovascular responses in conscious WAG/Rij rats with absence epilepsy. Intracerebroventricular administration of 0.3 and 0.5 nmol of bicuculline produces an increase in blood pressure and a slight bradycardia in non-epileptic Wistar rats. The blood pressure response to intracerebroventricular bicuculline is significantly potentiated in epileptic WAG/Rij rats. Bilateral lesions of the basolateral nucleus of the amygdala of WAG/Rilj rats completely prevent the presser response to 0.5 nmol of bicuculline, whereas unilateral lesion of the basolateral nucleus does not affect blood pressure changes in epileptic WAG/Rij rats. Additionally, the presser effect of 0.5 nmol of bicuculline is not attenuated by bilateral electrolytic ablation of the central nucleus of the amygdala in WAG/Rij rats. Heart rate response to bicuculline is not significantly changed in the lesioned groups. These findings indicate (a) altered GABAergic function in blood pressure regulation; and (b) a critical role of the basolateral nucleus in GABA(A)-mediated blood pressure control in epileptic WAG/Rij rats. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: absence seizures; cardiovascular; intracerebroventricular bicuculline; AMYGDALOID NUCLEUS; WAVE DISCHARGES; EPILEPSY; RESPONSES; THALAMUS; HYPOTHALAMUS; PROJECTION; MUSCIMOL; NEURONS; SPIKE